Experimental study of the effect of different pouring thicknesses on ice surface characteristics in the layered ice making process for speed skating - Liang, Y.; Song, M.; Uglanov, D. A.; Zhang, X.; Shao, K.; Zhen, Z. (Applied Thermal Engineering, 2025)
With the global popularity and competitive level of ice and snow sports, speed skating has also attracted widespread attention. In the speed skating ice making process, the thickness of ice pouring is a key factor affecting the quality of the ice surface. To understand the effect of different ice thickness on speed skating ice surface, speed skating ice freezing experiments with different ice thickness have been carried out. The results of the study showed that the total ice making time decreased as the thickness of the poured ice increased. The total ice making time decreased by 45.2 % when the thickness of poured ice was increased from 1 mm to 5 mm. Layered ice pouring will cause the bubbles inside the ice to form layers, with egg-shaped trapped air bubbles at the bottom of each layer and needle-shaped trapped air bubbles in the upper layer. As the thickness of the ice poured increases, the air content of the ice increases and the transparency decreases. In addition, when the ice thickness was reduced from 5 mm to 1 mm, the hardness of the ice increased by 49.3 %. This study is expected to provide a scientific basis for the design and maintenance of speed skating rinks, and further emphasizes the importance of ice surface quality in enhancing sports performance and ensuring the safety of athletes.